2021
DOI: 10.1109/access.2021.3056025
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers to Implementation of Connected, Automated, Shared, and Electric Vehicles: An Agenda for Future Research

Abstract: Several converging trends appear to reshape the way citizens and goods move about. These trends are social, including urbanization and population growth, and technological, such as increased automation and connectivity. All these factors influence the market for connected, automated, shared and electric (CASE) vehicles, which presents many opportunities and challenges. The pace of the shift to a profoundly penetrated market for CASE vehicles is far from secure. Such transformation depends on the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The noticeable percentage of distracted young drivers at intersections indicates that this issue needs urgent attention to prevent the occurrence of these crashes. The effects of state-of-the-art technologies to improve the attentiveness of young drivers while driv-ing and provide them with modern onboard devices to avoid distraction have been studied [70][71][72]. For instance, the connected vehicle (CV) and driving assistance (DA) technologies have the ability to reduce 94% of crashes in the U.S. that are due to either human error or bad/wrong decisions [73].…”
Section: Regression Analysismentioning
confidence: 99%
“…The noticeable percentage of distracted young drivers at intersections indicates that this issue needs urgent attention to prevent the occurrence of these crashes. The effects of state-of-the-art technologies to improve the attentiveness of young drivers while driv-ing and provide them with modern onboard devices to avoid distraction have been studied [70][71][72]. For instance, the connected vehicle (CV) and driving assistance (DA) technologies have the ability to reduce 94% of crashes in the U.S. that are due to either human error or bad/wrong decisions [73].…”
Section: Regression Analysismentioning
confidence: 99%
“…A systematic safety assessment framework is needed to standardize the AT operations, reduce potential risks, and enhance the overall reliability. 15 Trentesaux et al…”
Section: General Issues Associated With Autonomous Trainsmentioning
confidence: 99%
“…Similarly, contextual factors such as purchase prices, incentives [11], level of familiarity [12], and travel and waiting times [13] have an impact on the willingness to use autonomous shuttles. One of the most important aspects for acceptance, however, is the perceived safety regarding AVs [5,[14][15][16][17][18][19]. As Level 4 and especially Level 5 AVs would be a new form of transport with the lack of a human driver, users need to trust and feel secure in driverless shuttles as a necessary prerequisite of acceptance (as research on the acceptance of automated systems has shown [20]).…”
Section: Introductionmentioning
confidence: 99%